2010
DOI: 10.1186/1471-2415-10-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of alternate outreach models for cataract services in rural Nepal

Abstract: BackgroundBharatpur Eye Hospital in Chitwan District, a primarily agrarian setting in south-central Nepal, reduced the number of diagnostic screening and treatment (DST) camps by one half (151 to 75) in an attempt to increase both the efficiency of its outreach program and the number of people that go directly to the hospital for service. The Hospital evaluated the two program models in terms of program costs, cataract surgical utilization, hospital direct payment and patient equity.MethodsThe study is a prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…As noted above, there is a lack of research in this area, although the work of MICDA (2008) over the past ten years in Chitwan, is a notable exception. A few studies exist that explore the health needs of the elderly in relation to conditions such as uterine prolapse (Bonetti et al, 2004), cataract services (Kandel et al, 2010), parasitic infections (Shakya et al, 2006) however, overall there is a paucity of research into the health needs of the elderly in Nepal. One study examines metabolic syndrome amongst inmates of a home for the aged (Pemminati et al, 2009) and another on self-reported health problems of the elderly (Kshetri and Smith, 2010).…”
Section: Health Considerations Of the Changing Population Structure Imentioning
confidence: 99%
“…As noted above, there is a lack of research in this area, although the work of MICDA (2008) over the past ten years in Chitwan, is a notable exception. A few studies exist that explore the health needs of the elderly in relation to conditions such as uterine prolapse (Bonetti et al, 2004), cataract services (Kandel et al, 2010), parasitic infections (Shakya et al, 2006) however, overall there is a paucity of research into the health needs of the elderly in Nepal. One study examines metabolic syndrome amongst inmates of a home for the aged (Pemminati et al, 2009) and another on self-reported health problems of the elderly (Kshetri and Smith, 2010).…”
Section: Health Considerations Of the Changing Population Structure Imentioning
confidence: 99%
“…Only a handful of studies have examined the costs of other case finding strategies such as health facilities 29 , 30 or community outreach. 31 , 32 In these instances, the geographical scope has been limited to a particular facility, hospital or locality with uncertainty about how these might generalize at scale.…”
Section: Introductionmentioning
confidence: 99%